Association between 8 P‐glycoprotein (MDR1/ABCB1) gene polymorphisms and antipsychotic drug‐induced hyperprolactinaemia. Issue 9 (6th April 2020) - Geers, Lisanne M.; Pozhidaev, Ivan V.; Ivanova, Svetlana A.; Freidin, Maxim B.; Schmidt, Amand F.; Cohen, Dan; Boiko, Anastasiia S.; Paderina, Diana Z.; Fedorenko, Olga Yu; Semke, Arkadiy V.; Bokhan, Nikolay A.; Wilffert, Bob; et al.
Abstract : Introduction: Hyperprolactinaemia, a common adverse effect of antipsychotic drugs, is primarily linked to blockade of dopamine D2 receptors in the pituitary gland. Certain antipsychotic drugs, such as, for example risperidone and paliperidone, are more likely to induce hyperprolactinaemia compared to others. This effect is probably caused by a relatively high blood/brain concentration ratio, a consequence of being a substrate of P‐glycoprotein. Genetic variants of P‐glycoprotein with changed functional activity might influence the potential of risperidone and paliperidone to cause hyperprolactinaemia as the altered blood/brain concentration ratio would lead to a reduced therapeutic drug level within essential brain areas making dose adaptations necessary. This increases exposure of dopamine D2 receptors within the pituitary gland. Aims: To investigate possible associations between MDR1/ABCB1 gene polymorphisms and antipsychotic drug‐induced hyperprolactinaemia in Russian patients with schizophrenia and to determine possible differences between risperidone/paliperidone and other antipsychotics. Methods: In total, 446 patients with schizophrenia were included from 3 psychiatric hospitals in Siberia. Blood samples were obtained in a cross‐sectional study design for DNA extraction and prolactin measurement. Associations between hyperprolactinaemia and 8 MDR1/ABCB1 gene‐polymorphisms were assessed using logistic regression analysis accounting for covariates. The analysis was repeated in a patient subgroup using risperidone or paliperidone. Results: We did not observe an association between any of the 8 single nucleotide polymorphisms and the prevalence of antipsychotic‐induced hyperprolactinaemia in the total patient population. However, in the risperidone/paliperidone subgroup, the single nucleotide polymorphism rs2032582 (G2677T) was found to be negatively associated with risperidone/paliperidone‐induced hyperprolactinaemia. Conclusion: This study revealed a significant association between the ABCB1 gene polymorphism rs2032582 (G2677T) and risperidone/paliperidone‐induced hyperprolactinaemia.